Kajian Pembangunan Ketahanan Pangan Keluarga Petani - Amiruddin Ketaren; Rakhmadsyah Putra Rangkuty (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2021)
Indonesia is an agricultural country. The reality is that the agriculture sector is often secondary or not a top priority. Government policies are more likely to support the industrial sector, while the younger generation tends to leave the agricultural sector. That has an impact on decreasing the level of community food security. Rice imports are still being carried out today. Various factors encourage the problem of food insecurity in Indonesia. This literature review intended to map some problems in agriculture. Various reference sources from books and scientific works were collected and analyzed. Certain aspects, particularly those related to the economy and socio-culture, are dissected and elaborated to produce a comprehensive input for policy breakthroughs in development in the agricultural sector. The estuary is an increase in food security that means an increase in welfare.ABSTRAKIndonesia adalah negara agraris. Realitasnya sektor pertanian acapkali dinomorduakan atau tidak menjadi prioritas utama. Kebijakan pemerintah lebih cenderung mendukung sektor perindustrian, sementara generasi muda mulai meninggalkan sektor pertanian. Hal itu berdampak pada menurunnya tingkat ketahanan pangan masyarakat. Impor beras masih dilakukan hingga saat ini. Berbagai faktor mendorong terjadinya masalah kerawanan pangan di Indonesia. Kajian literatur ini dimaksudkan untuk memetakan permasalahan di bidang pertanian secara umum. Berbagai sumber rujukan dari buku dan karya ilmiah dikumpulkan dan dianalisis. Aspek-aspek tertentu, khususnya yang terkait dengan ekonomi dan sosio-kultural dibedah dan dielaborasi guna menghasilkan suatu masukan terobosan kebijakan yang komprehensif dalam pembangunan di bidang pertanian. Muaranya adalah peningkatan ketahanan pangan yang berarti peningkatan kesejahteraan.